Development of Student Worksheet Based on Guided Inquiry Assisted by Phet Simulation to Improve Concept Comprehension - Fatihah Nur Amini; Ekosari Roektiningroem; Insih Wilujeng (Journal of Science Education Research, 2022)
This study aimed to develop a product in the form of student worksheet based on the guided inquiry assisted by PhET simulation media on Vibration and Wave materials that was feasible according to validators, practical according to science teacher and student responses, and effective to improve student’s concept comprehension. This study was a research and development (R and D), which was adapted from Thiagarajan’s 4D model. The main field-testing was conducted at SMPN 2 Sukoharjo via online upon 12 students of class VIII H. The design of the main field-testing was one group pre-test-post-test design. The analysis technique included the mean score, Meltzer’s standard gain test and Cohen’s effect size test. The results show that (1) the obtained student worksheet product based on guided inquiry assisted by PhET simulations was feasible according to the material and media experts with an excellent category, (2) the practicality of the student worksheet used by science teacher was in an excellent category and obtained good responses from the students, and (3) the effectiveness of the developed student worksheet was able to improve concept comprehension with a gain score in the moderate category and the effect size was categorized as a strong effect.